Tinjauan Tentang Perkembangan Pengaruh Local Genius Dalam Seni Bangunan Sakral (Keagamaan) Di Indonesia - Joko Budiwiyanto (Institut Seni Indonesia Surakarta, 2005)
Cultural value-system which is formed by local genius has major influence in the development of shrine in Indonesia. To analyze the improvement, we can observe the acculturation process between Indonesian original cultures with the foreign culture. This acculturation process will constructed a new culture without dispatching the original culture. The obvious example of this process could be found through shrine’s physical characters which reflected the Indonesian cultural heritage and also the growth of Indonesian local genius. This paper will explore the development of local genius’s influence to the architecture of Indonesian’s shrine in every historical periodicity. The periodicity discussed will begin from pre-historic, ancient, madya to modern era. This paper will also discussed the prominent holy places serve also as cultural creations - of every era such as menhir, punden berundak, temple, mosque, and church along with the influential value system.Key word: Local genius, acculturation